(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The aim of the present review provides the relationship between therapeutic nanoparticles and mononuclear phagocytic system. Reticuloendothelial system (RES) represents a group of cells having the ability to take up and sequester inert particles and vital dyes. This includes macrophages and macrophage precursors, specialized endothelial cell lining the sinusoids of the liver, spleen and bone marrow, and the reticular cell of the lymphatic tissue (macrophages) and of the bone morrow (fibroblast). Nanoparticles are rapidly sequestered and retained by the organs comprising of the reticuloendothelial system (RES), mainly the liver, spleen and the bone marrow. Thus, targeting of the nanoparticles to the reticuloendothelial system (RES) is much simpler than to any other organ. In the liver, the particles are mainly retained by the scavenging periportal and midzonal Kupffer cells, while the hepatocytes and liver endothelial cells may play a secondary role under special pathophysiological conditions or for special physic- chemical characteristics of particles. The clearance of conventional nanoparticles has been proposed to occur by uptake of the nanoparticles by the reticuloendothelial system (RES). The mononuclear phagocytic system uptake of nanoparticles results in their rapid removal from the blood and accumulation in tissues involved in the RES, such as the liver and spleen. Uptake by the RES usually results in irreversible sequestering of the encapsulated drug in the RES, were it can be degraded. In addition, the uptake of the nanoparticles by the RES may result in acute impairment of the mononuclear phagocytic system and toxicity. Sterically stabilized nanoparticles, such as STEALTH nanoparticles, prolong the duration of exposure of the encapsulated nanoparticles in the systemic circulation. The presence of the PEG coating on the outside of the nanoparticles does not prevent uptake by the reticuloendothelial system, but simply reduces the rate of uptake.